WOMEN SAFETY ANALYTICS-PROTECTING WOMEN FROM SAFETY THREAT (Lex localis - Journal of Local Self-Government, 2025)
WSafe is an innovative Android-based personal safety application specifically designed to address the critical need for women's security in today's society. This comprehensive mobile solution leverages modern smartphone capabilities to provide immediate assistance during emergency situations through a multi-faceted approach to personal safety. The application integrates advanced features including motion-based emergency triggers through shake detection, real-time GPS location tracking, automated SOS messaging, and an emergency siren system. What distinguishes WSafe is its holistic approach to women's safety, combining immediate emergency response features with preventive measures such as access to self-defense tutorials, legal resources regarding women's rights, and a curated directory of national helplines. The application's architecture is built on Java using Android Studio, ensuring robust performance and reliability across Android devicesBy incorporating both active security measures and educational resources, WSafe not only provides immediate assistance during emergencies but also empowers users with knowledge and tools for long-term safety awareness. The implementation of location-based services enables users to quickly locate nearby police stations and hospitals, while the panic button feature ensures one-touch access to emergency contacts. This project represents a significant step forward in leveraging mobile technology to create a more secure environment for women, offering both immediate emergency response capabilities and tools for long-term safety empowerment.